2015
DOI: 10.1159/000381902
|View full text |Cite
|
Sign up to set email alerts
|

What Have Mass Spectrometry-Based Proteomics and Metabolomics (Not) Taught Us about Psychiatric Disorders?

Abstract: Understanding the molecular causes and finding appropriate therapies for psychiatric disorders are challenging tasks for research; -omics technologies are used to elucidate the molecular mechanisms underlying brain dysfunction in a hypothesis-free manner. In this review, we will focus on mass spectrometry-based proteomics and metabolomics and address how these approaches have contributed to our understanding of psychiatric disorders. Specifically, we will discuss what we have learned from mass spectrometry-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 79 publications
(92 reference statements)
0
11
0
Order By: Relevance
“…Multi-omics approaches have the potential to shed light on molecular mechanisms of psychiatric disorders in a high-throughput and data-driven manner (Filiou, 2015). Metabolomic analyses provide valuable information for dissecting neuropsychiatric conditions, as the metabolome correlates directly with the phenotype and is very sensitive to environmental stressors and changes (Quinones and Kaddurah-Daouk, 2009; Turck and Filiou, 2015). Metabolomic approaches have been used to study depression both in patient cohorts and animal models (Pan et al, 2018; Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Multi-omics approaches have the potential to shed light on molecular mechanisms of psychiatric disorders in a high-throughput and data-driven manner (Filiou, 2015). Metabolomic analyses provide valuable information for dissecting neuropsychiatric conditions, as the metabolome correlates directly with the phenotype and is very sensitive to environmental stressors and changes (Quinones and Kaddurah-Daouk, 2009; Turck and Filiou, 2015). Metabolomic approaches have been used to study depression both in patient cohorts and animal models (Pan et al, 2018; Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies applying metabolomic profiling of patient serum are also starting to be used to explore the biology of psychiatric disorders [41,42,43,44,45,46]. Such studies have suggested the possibility of identifying biomarkers for schizophrenia [47,48,49,50,51,52], major depressive disorder [53,54] and posttraumatic stress disorder [55], and have also been used to study medication-induced metabolic changes [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…In this review, neuropsychiatric disorders are restricted to anxiety, depression, bipolar disorder and schizophrenia which encompass most of the known symptoms in this group of diseases. Accurate diagnosis and treatment of these disorders is hindered by their etiological and clinical heterogeneity [116], hence the need for more reliable biomarkers as well as therapeutic interventions. Genomic studies have dominated neuropsychiatric research in the last decade and improved our understanding of mental diseases [117][118][119][120][121][122].…”
Section: Dynamics Of Processes In Neuropsychiatric Disordersmentioning
confidence: 99%